Netflix, Inc. : risks of a new business model - Allen, Douglas (SAGE Knowledge. Cases., 2017)
After ten years of meteoric rises in revenue and subscription customers, a series of communication blunders has put Netflix in a perilous position. Netflix has mishandled key communications regarding account and fee changes affecting its customers. In three months, Netflix has since seen its company's stock price plummet more than 60 percent.